2003
DOI: 10.1021/ol034630s
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Synthesis of Pseurotin A

Abstract: The asymmetric total syntheses of pseurotin A and 8-O-demethylpseurotin A have been accomplished. Key reactions are a NaH-promoted intramolecular cyclization of an alkynylamide to form a gamma-lactam, an aldol reaction of a benzylidene-substituted ketone, and the late-stage introduction of the benzoyl group by a selective oxidation of a benzylidene moiety with dimethyldioxirane (DMD). [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…Its absolute configuration was determined by X-ray diffraction analysis of a dibromo derivative [ 1 ]. Most of the other γ-lactams were determined by asymmetric total synthesis [ 5 , 6 , 7 , 8 , 9 , 10 ] and the modified Mosher’s method [ 11 , 12 ]. Previously, we reported that all stereoisomers of FD-838 showed an association between the CD Cotton effect and the absolute configuration of the chiral centers in γ-lactam [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its absolute configuration was determined by X-ray diffraction analysis of a dibromo derivative [ 1 ]. Most of the other γ-lactams were determined by asymmetric total synthesis [ 5 , 6 , 7 , 8 , 9 , 10 ] and the modified Mosher’s method [ 11 , 12 ]. Previously, we reported that all stereoisomers of FD-838 showed an association between the CD Cotton effect and the absolute configuration of the chiral centers in γ-lactam [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple transformations starting from the intermediate 395 subsequently furnished the final natural products pseurotin A and 8-O-demethylpseurotin A (Scheme 84). [79] In 2007, Crone and Kirsch reported two reactions utilizing 2-alkynyl-2-silyloxy carbonyl compounds for the synthesis of 4iodo-3(2H)-furanones (Scheme 85). The first reaction follows an electrophilic cyclization pathway induced by N-iodosuccinimide while the second proceeds as a gold catalyzed tandem reaction followed by 1,2-migration.…”
Section: Methods For the Synthesis Of 245-trisubstituted-3(2h)-furamentioning
confidence: 99%
“…Hayashi's group achieved the total syntheses of azaspirene (133), 66 pseurotin A (134), 67 and synerazol (137) 68…”
Section: -1 Hayashi's Total Syntheses Of (−)-Azaspirene Pseurotin a And Synerazolmentioning
confidence: 99%